Role of nitrogen metabolites on the regulation of nitrate uptake in maize seedlings - Pal'ove-Balang, Peter (Acta Biologica Szegediensis, 2002)
The ability of individual amino acids to regulate nitrate uptake was studied in Zea mays L. seedlings. The amino acids were applied to the root media or supplied by immersion of the tip-cut leaves before the induction of inducible high-affinity transport system with 0.1 mM KNO3. NO3- uptake was measured by its depletion in amino acid – free medium. Glutamine and glutamate applicated via roots, were found to be the most effective inhibitors of uptake processes. The treatment with Gln via leaves also resulted in a strong inhibition of nitrate uptake rate accompanied with the significant enrichment of root tissue by amino compounds. Exclusion of conversion of glutamine to glutamic acid and to other amino acids by aminooxalacetic acid has showed, that with high probability the glutamine is responsible for the observed nitrate uptake inhibition. Since the lag-phase in inhibitory effect of glutamine was shorter than 2 hours, we suppose the direct inhibition of glutamine on the nitrate carrier itself, rather than on the corresponding gene expression.